Determination of Sulfamethoxazole in Pure and Pharmaceutical Samples by Using Direct Method for Calibration Curve of Normal Spectrum of UV-Spectrophotometry - A. Abrahem, Sarra; H. Al-Saidi, Khaleda (Al-Nahrain Journal of Science, 2020)
Normal spectra for sulfamethoxazole solutions were developed and used for the determination of sulfamethoxazole (SMX) antibiotic by using zero-crossing technique and simultaneously determining (SMX) at wavelength 259.00 nm. The correlation coefficient of the calibration curve for the normal spectrum was 0.9990. Linearity was maintained by using concentrations (0.990´10-4 M, 0.996´10-4 M, 0.999´10-4 M, 1.004´10-4 M, 1.005´10-4 M) and the percentage recovery of sulfamethoxazole samples were (99.00%, 99.60%, 99.90 %, 100.40 % and 100.50 %). A statistical analysis confirmed, a precision with accuracy for simultaneous fixing of (SMX). In addition, a British pharmacopoeia method was compared with the method used in this paper using F test.